Purification and molecular characterization of a Metschnikowia saccharicola killer toxin lethal to a crab pathogenic yeast. Issue 10 (15th February 2018) - Tan, Chunming; Wang, Lin; Xue, Yong; Lin, Shuo; Yu, Gang; Yang, Shaoling
Abstract: The marine yeast strain Metschnikowia saccharicola DD21-2, isolated from sediments in the Yalu River, produces a killer toxin with a lethal effect on Metschnikowia bicuspidate strain WCY, a pathogenic yeast strain that infects crabs. In this study, the killer toxin was purified and characterized. After sequential purification, the purity of the killer toxin was increased 72.2-fold over the purity of the yeast cell culture supernatant. The molecular weight of the purified killer toxin was 47.0 kDa. The optimal pH and temperature for killing activity were 5.5°C and 16°C, respectively. The killing activity was stable over a pH range of 4.0–6.5 and temperature range of 0°C–40°C. The purified killer toxin was only effective against toxin-sensitive integral cells and had no killing effect on the protoplasts of toxin-sensitive cells. When exerting the killing effect, the toxin bind to a cell wall receptor of the treated strain, disrupted cell wall integrity and eventually caused death. The amino acid sequence identified by mass spectroscopy indicated that the purified killer toxin might be a protein kinase, but did not show β-1, 3-glucanase activity, consistent with the laminarin hydrolysis results. These findings provide a basis for disease prevention and control in marine aquaculture. Abstract : Yeast killer toxin from Metschnikowia saccharicola .